Sports and recreational activities - Mood, Dale (WCB/McGraw-Hill, 1999)
Featuring fundamental information on 42 different sports and recreational activities, this text includes an overview of all aspects of each sport, including history, equipment, rules, fundamental skills, techniques, etiquette, strategy and more.